2016
DOI: 10.1155/2016/2153910
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Species of Nontuberculous Mycobacteria Clinical Isolates from 8 Provinces of China

Abstract: Pulmonary diseases caused by nontuberculous mycobacteria (NTM) are increasing in incidence and prevalence worldwide. In this study, we identified NTM species of the clinical isolates from 8 provinces in China, in order to preliminarily provide some basic scientific data in the different species and distribution of NTM related to pulmonary disease in China. A total of 523 clinical isolates from patients with tuberculosis (TB) diagnosed clinically from 2005 to 2012 were identified to the species using convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Interestingly, the occurrence of Gordonia is similar to some report in China [22]. Two Nocardia which often cause chronic lung diseases were isolated, as reported in the several article in China [23]. In addition, Tsukamurella infection case in Jiangxi province has previously been reported in in Southern-central China [6].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, the occurrence of Gordonia is similar to some report in China [22]. Two Nocardia which often cause chronic lung diseases were isolated, as reported in the several article in China [23]. In addition, Tsukamurella infection case in Jiangxi province has previously been reported in in Southern-central China [6].…”
Section: Discussionsupporting
confidence: 73%
“…In another research from Guangdong and Shanghai province proved that M. intracellulare was the most commonly isolated NTM in Shanghai and the most frequently isolated species in Guangzhou is M. abscessus [22]. Some researches in eastern and northern region of China demonstrated the NTM prevalence rate is around 2.0%-3.0% and the predominated species is M. intracellulare, followed by M. abscessus [5,[21][22][23]. In our study, the NTM infection is more prevalent in southern than northern China and is more frequently in eastern than western China.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the most common NTM was represented by MAC strains, similar to the epidemiology of NTM in China and in many regions in the world. The predominant species among MAC in this study was M. chimaera, while M. intracellulare was the main one in other regions of China [15,16,23]. In addition, the M. colombiense and M. lentiflavum found in this study were hardly reported in China, indicating that some species of NTM were underestimated in clinical samples [23].…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, M. chimaera could not be easily distinguished from the M. intracellulare based on 16S rRNA and rpoB sequencing, causing incorrect species identification by commonly used laboratory techniques [24,25]. Therefore, the common identification methods based on 16S rRNA in China may lead to an underestimated prevalence of M. chimaera [15,16,19]. In addition, the species varies across the different regions as reported, which may be explained by the heterogeneities in exposure routes and susceptibility of individuals [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation